Las gramineas (Poaceae) del estado de Zulia, Venezuela. Lista de los generos presentes - Pacheco Rivera, D.=700 1 Zambrano, J.O.; Sthormes, G.
(Es, En)
Ilus., 22 ref.
Keywords: TAXONOMIA; GRAMINEAS; POACEAE; GENERA; VENEZUELA